Compulsory schooling laws and the cure against child labor - Giorgio Bellettini; Carlotta Berti Ceroni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
Equally, poor countries display similar compulsory schooling laws but different levels of child labor and school attendance. This paper provides an explanation for the existence of child labor, which relies on the imperfect enforcement of compulsory schooling laws and is consistent with the above cross-country differences. In the presence of complementarities in the production of human capital that justify legislative intervention, mandatory measures ensure that coordination failures are solved so that all parents send their children to school and the socially optimal equilibrium is reached. However, if enforcement of legislation is too low, multiple equilibria emerge. In this case, child labor occurs more often among poor households, and compulsory schooling laws may have adverse welfare effects.
Keywords: 330